Datura innoxia anti-angiogenesis properties - B. Khoshkhoo; S. Mohammadi Motamed; M. Hamzeloo-Moghadam (Iranian Society of Pharmacognosy, 2017)
Background and objectives: Datura innoxiaMilleris one of the two species of Datura (Solanaceae) which grow in Iran. There are many reports of the biological activities of Datura and in the present study the ability of Datura innoxia for inhibiting angiogenesis was evaluated. Methods: The methanol extract and petroleum ether, chloroform and methanol fractions of Datura innoxia flowers were obtained by maceration method. The extract and fractions were further evaluated for their cytotoxicity and anti-angiogenesis properties in HUV-EC-C cells through MTT and wound healing assays, respectively. Results: The methanol extract and the petroleum ether, chloroform and methanol fractions were cytotoxic to HUV-EC-C cells (IC50 11.25, 63.3, 8.75 and 9.27 μg/mL, respectively). The chloroform fraction demonstrated the most anti-angiogenesis activity in the wound healing assay. Conclusion: Evaluating the above activities of the compounds isolated from Datura innoxia might be a proper follow up of the present study.